Famílias incorporadas à Política Nacional de Assistência Social: estudo das repercussões do benefício de prestação continuada - BPC em suas vidas - Rossi, Cássia Mazeti (2013)
This present job has the aim of analyzing the repercussions and expressive significations in the life of three families that are introduced in the Straight Transference of Income Program: The Continued Installment Benefit: CIB. The main subject of analysis was to observe the feelings lived by the beneficiaries families after been included and receiving financial resource. With the realization of a qualitative study about the three chosen families for the research, it was able to recognize the aspects understood by them as important in the benefit concession. Their ways of understanding the use of such value, as well as the use of priorities and positives repercussions in the everyday life were also analyzed. According to the interwiers‟ expectations and perceptions, the subjectivity in this dissertation was extensively worked and analyzed. The subjects of this research were extended families that also realize the function of caring the family member which has the profile of the CIB beneficiary; so that it was elaborated in order to prioritize the speech of the interviewers. Concerning to the obtained results,it was relevant the achieved information regarding to the occurred modifications pos-receiving and which providences these families adopted, like, the priority in use and in the first instance, the satisfaction of the basic necessities, avoiding the lack of food in the everyday life. Two, among the three interviewed, noticed significant improvements in their lives in the material point of view, as well as in the subjectivity of family relations. Only, one of the interviewers, mentioned not having noticed significant modifications. Finally, this task showed its importance for having to research the life of three beneficiaries families from the CIB Program, which is introduced in the Social Assistance like Public Politics, proving being important to compose the Social Protection in the country. Even though the access isn‟t all over the world, the program brought in the studied cases, assurance of improvement in the life of these families